Relationship between Information Disclosure Quality and Financial Risk: Evidence from Shenzhen A-share - Lai, Yangyang (2022)
The quality of information disclosure has always been a hot issue in the academic field. Based on MM theory, trade-off theory, the efficient market hypothesis, information asymmetry theory, pecking order theory, and principal-agent theory, this research chose Shenzhen A share mainboard data from 2005 to 2019 as samples, using the DID model to have empirical research to find the relationship between quality of information disclosure and firms’ financial risk. This paper selected 251 manufacturing companies and 41 real estate companies and tested the effect of the implementation of information disclosure policies on the reduction of corporate financial risks.